Da contra-hegemonia política às políticas contra-hegemônicas: as ações afirmativas para negros na sociedade brasileira - Marcelo Martins Silva; Ramatis Jacino; Sidney Jard Silva (Ciências Sociais Unisinos)
The presence of blacks in valued spaces in Brazilian society is characterized by their under-representation. This aspect was historically hegemonic in the projects of nation elaborated in the country. Despite this, the black population produced counter-hegemonic institutions and actions at different times. We argue that affirmative action for blacks in Brazil appears as one of those counter-hegemonic perspectives in the recent political scenario. This article intends to discuss how the country’s racial hegemony was established; the resistance of the black community and the role of affirmative action for the black population in the scope of a racial counter-hegemony. Through a theoretical discussion and secondary data, we conclude that affirmative actions for blacks in Brazil are one of the most relevant strategies today to break with the hegemonic patterns of brazilian race relations.